OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN GEOGRAPHIC ATROPHY. Issue 12 (December 2018) - Sacconi, Riccardo; Corbelli, Eleonora; Carnevali, Adriano; Querques, Lea; Bandello, Francesco; Querques, Giuseppe
Abstract : Purpose: To analyze choriocapillaris (CC) vessel density (VD) around geographic atrophy (GA) secondary to non-neovascular dry age-related macular degeneration using optical coherence tomography angiography. Methods: We compared CC VD surrounding GA margin (500 μ m radius) with control CC (outside GA margin) in a consecutive series of GA patients presenting between August 2016 and February 2017 at the Medical Retina and Imaging Unit of University Vita-Salute, IRCCS Ospedale San Raffaele in Milan. Images were obtained through thresholding and binarization. We also compared the CC VD in a sample area of 500 μ m × 500 μ m surrounding GA margin rated as hyperautofluorescent on fundus autofluorescence to a similar area rated as isoautofluorescent. Results: Fifty eyes of 29 patients (19 women and 10 men; mean age 77 ± 6 years) with mean GA area of 9.43 ± 5.08 mm 2 and mean subfoveal choroidal thickness of 164 ± 73 μ m were included. Choriocapillaris VD surrounding GA margin as detected by optical coherence tomography angiography revealed a significant impairment compared with control CC outside GA margin (0.317 ± 0.083 vs. 0.461 ± 0.054, P < 0.001), which was even greater in patients with foveal involvement ( P = 0.013). Furthermore, mean VD in hyperautofluorescent areas was significantly lower compared with isoautofluorescent areas (0.242 ± 0.112 vs. 0.327 ± 0.130, P = 0.001). A positive correlation was disclosed between VD surrounding GA margin and subfoveal choroidal thickness (r = 0.332, P = 0.019). Conclusion: Optical coherence tomography angiography discloses CC impairment surrounding GA margin. Such CC impairment at GA margin seems to precede retinal pigment epithelium alterations at fundus autofluorescence. Optical coherence tomography angiography could be a new valuable tool for detecting CC alterations and to evaluate potential therapeutic responses in clinical studies. Abstract : This study was conduced to evaluate the vessel density of choriocapillaris around geographic atrophy secondary to non-neovascular dry age-related macular degeneration using optical coherence tomography angiography. The authors found a significant choriocapillaris impairment surrounding geographic atrophy margin, which seems to precede retinal pigment epithelium alterations at fundus autofluorescence.